Analisis Peta Mutu Pendidikan SMA Kabupaten Lombok Tengah Tahun 2020 - Mohamad Tohar (Universitas Pendidikan Mandalika, 2022)
The purpose of this study is to produce a portrait of the educational quality of Central Lombok High School in 2020 through the process of data collection, environmental analysis, as well as recommendations and quality improvement strategies referring to the results of mapping the quality of education in order to be an inspiration for education units and local governments in implementing SPMP. properly and sustainably. The research method used is descriptive qualitative. This research data collection includes 2020 quality report cards sourced from Dapodik (dapodikdasmen.kemdikbud.go.id) and data sourced from PMP (pmp.dikdasmen.kemdikbud.go.id). Based on the results of the analysis of the high school education quality map, it was concluded that none of the senior high schools